Mitral valve lesion associated with secundum atrial septal defect. Analysis by real time two dimensional echocardiography. Issue 1 (January 1983) - Nagata, S; Nimura, Y; Sakakibara, H; Beppu, S; Park, Y D; Kawazoe, K; Fujita, T
Abstract : Mitral valve lesions accompanying secundum atrial septal defect were examined in 120 successive patients from May 1978 to December 1980 using real time two dimensional echocardiography. The conclusions were as follows: (1) The characteristic feature of the mitral lesion accompanying secundum atrial septal defect is a dislocation of the mitral leaflet toward the left atrial side in the area of coaptation. (2) The mitral lesion is seen in about half the patients with secundum atrial septal defect. (3) It is usually seen only in the anterior leaflet, and is found near the posteromedial commissure. Lesions in other sites on the leaflet all accompany those near the posteromedial commissure. (4) The incidence, extent, and degree of the mitral valve lesion increase with age. (5) It is assumed that the mitral valve lesion in secundum atrial septal defect starts near the posteromedial commissure in the anterior leaflet, gradually deteriorates, and extends toward the anterolateral commissure. (6) It is probable that the mitral lesion results in mitral regurgitation. (7) The mitral valve lesion is similar in appearance to mitral valve prolapse caused by the floppy mitral valve, though their causative factors may be different. It is probably the reason why the mitral valve abnormality has been described as mitral valve prolapse in previous reports. In the present study the mitral lesion was evaluated on the distance of the dislocation between both leaflets at the area of coaptation. These criteria proved useful. Because of the similarity in appearance, it may be helpful in the assessment of primary mitral valve prolapse.